PENGARUH KUALITAS LAYANAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS LAYANAN PADA KOPERASI GURU MMI (KAGUMI) PONDOK PESANTREN DAAR EL-QOLAM GINTUNG KECAMATAN JAYANTI TANGERANG - Iwan Ridwan; M. Zainal Rosid (Universitas La Tansa Mashiro, 2018)
The supervisor in preparing this thesis is Mr. Dr. Yumhi, S., M.M and Dr. Wildan, S.I.P., M.M.This study aims to determine the effect of service quality and customer satisfaction on the MMI (Kagumi) Teacher Cooperative in Daar el-Qolam Islamic boarding school.The population in this study were all customers in the MMI (Kagumi) Teacher Cooperative according to grade level from grade 1 to 6 (1 junior high school to 3 high school) as many as 3077 students male and female students. Whereas the questionnaires were 337 male/female students of 6/3 high school Daar el-Qolam Islamic Boarding School, a sample of 91 people and as many as 28 from goods suppliers were taken using the Proportionate Stratified Random Sampling technique using the Yamane Rakhmad formula which states that if population of more than 100, the sample taken is 10% or more. Data retrieval techniques used method of documentation/questionnaire (questionnaire) to determine the effect of service quality on customer satisfaction. This research method is a quantitative method. Data analysis using Multiple Regression Analysis.Correlation calculation results show a very strong relationship where service quality (Variable X1) and customer satisfaction (Variable X2) is related to service loyalty (Variable Y). The results of the calculation of the coefficient of determination show that service quality and customer satisfaction will increase service loyalty. And the results obtained from this study can be concluded that service quality and customer satisfaction have a significant positive effect on service loyalty of MMI (Kagumi) Teacher Cooperative Daar el-Qolam Islamic Boarding School, Gintung Jayanti Tangerang.